THE ROLE OF TEACHING RUSSIAN LANGUAGE IN NATIONAL GROUPS - Tokhta Ametovna Yuldasheva (Galaxy International Interdisciplinary Research Journal, 2022)
This article examines the role of the Russian language in the modern world, it also talks about the Russian language as a language of international importance, and the importance of the Russian language in the postSoviet space.